Intention to Buy Halal Cosmetics based on Social Media Activities, Brand Equity, and e-WOM - Syifa Rofifa Putri Rizq; Istyakara Muslichah (Universitas Airlangga, 2023)
ABSTRACT This study aimed to analyze the impact of social media marketing activities on the intention to buy halal skin care products because previous studies showed that there were still inconsistencies in the findings regarding what factors can influence consumer buying interest. This study used a quantitative approach with purposive sampling technique. the sample criteria of this study was social media users who follow halal cosmetic's account with a total of 200 respondents. The data analysis technique used in this study was the PLS-SEM method. The variables in this study were social media marketing activities, brand equity, electronic Word Of Mouth, and purchase intention. The results of this study indicate that social media marketing activities have a positive effect on brand equity, brand equity has a positive effect on electronic word of mouth, and the relationship between electronic word of mouth is stated to be positive on purchase intention. However, social media marketing activities do not significantly affect purchase intentions. The contribution of this research is that entrepreneurs can be encouraged to pay attention to the potential of social media marketing activities in forming patterns of developing marketing strategies because they can affect brand equity, electronic word of mouth, which in turn can encourage purchase intentions for halal skin care products. Keywords: Social Media Marketing Activity, Brand Equity, electronic Word Of Mouth (e-WOM), Purchase Intention. ABSTRAK Penelitian ini bertujuan untuk menganalisis dampak aktivitas pemasaran media sosial pada niat beli produk perawatan kulit halal karena pada penelitian-penelitian sebelumnya masih terdapat ketidakkonsistenan pada hasil temuan mengenai faktor apa saja yang dapat mempengaruhi minat beli konsumen. Metode dalam penelitian ini menggunakan pendekatan kuantitatif. Dengan teknik sampel purposive, sampel penelitian ini adalah pengguna media sosial yang mengikuti media sosial produk perawatan kulit halal dengan jumlah 200 responden. Teknik analisis data yang digunakan penelitian ini memakai metode PLS-SEM. Variabel pada penelitian ini yakni aktivitas pemasaran media sosial, ekuitas merek, electronic Word Of Mouth, dan niat beli. Hasil penelitian ini menunjukkan bahwa aktivitas pemasaran media sosial berpengaruh positif terhadap ekuitas merek, ekuitas merek terhadap electronic word of mouth memiliki pengaruh positif. Hubungan antara electronic word of mouth dinyatakan positif terhadap niat beli. Akan tetapi, pengaruh aktivitas pemasaran media sosial tidak signifikan mempengaruhi niat beli. Kontribusi penelitian ini agar pelaku bisnis memperhatikan potensi aktivitas pemasaran media sosial dalam membentuk pola pengembangan strategi pemasaran karena dapat mempengaruhi ekuitas merek, electronic word of mouth, yang pada akhirnya dapat mendorong niat beli pada produk perawatan kulit halal. Kata Kunci: Aktivitas Pemasaran Media Sosial, Ekuitas Merek, electronic Word Of Mouth (e-WOM), Niat Beli REFERENSI Abdillah, W. (2018). Metode penelitian terpadu sistem informasi: permodelan teoritis, pengukuran dan pengujian statistis. Yogyakarta: Andi Adriani, L. (2020). Pengaruh Islamic Religiosity dan Halal Knowledge terhadap purchase intention kosmetik halal dimediasi oleh attitude terhadap produk halal di Indonesia. AL-MUZARA'AH, 8(1), 57–72. Ahmad, F., & Guzman, F. (2021). Brand equity, online reviews, and message trust: The moderating role of persuasion knowledge. Journal of Product & Brand Management, 30(4), 549–564. doi:10.118/JPBM-09-2019-2564 Aji, P., Nadhila, V., & Sanny, L. (2020). Effect of social media marketing on Instagram towards purchase intention: Evidence from Indonesia's ready-to-drink tea industry. International Journal of Data and Network Science, 4(2), 91–104. doi:10.5267/j.ijdns.2020.3.002 Alrwashdeh, M., Emeagwali, O., & Aljuhmani, H. (2019). The effect of electronic word of mouth communication on purchase intention and brand image: An applicant smartphone brands in North Cyprus. Management Science Letters, 9(4), 505–518. doi:10.5267/j.msl.2019.1.011 Amalia, F. A., Sosianika, A., & Suhartanto, D. (2020). Indonesian millennials' halal food purchasing: merely a habit? British Food Journal, 122(4), 1185-1198. doi:10.1108/BFJ-10-2019-0748 Ariffin, S. K., Azra, W. F., Wahid, N. A., & Nee, G. Y. (2019). Investigating the factors affecting purchase intention of muslim women towards halal cosmetics. Journal of Entrepreneurship, Business and Economics, 7(2s), 78–105. Boon, L. K., Fern, Y. S., & Chee, L. H. (2020). Generation Y's purchase intention towards natural skincare products: A PLS-SEM analysis. Global Business and Management Research: An International Journal, 12(1), 61–77. Choedon, T., & Lee, Y.-C. (2020). The effect of social media marketing activities on purchase intention with brand equity and social brand engagement: Empirical evidence from Korean cosmetic firms. The Knowledge Management Research Society of Korea, 21(3), 141–160. Dayoh, M. L., Ari, L., & Agrippina, Y. R. (2022). The effect of social media marketing activities to purchase intention. JUMMA: Jurnal Ilmiah Mahasiswa Manajemen, 11(1), 65–77. Fauzia, A. Z. N., & Sosianika, A. (2021). Analisis pengaruh brand image, perceived quality, dan country of origin terhadap minat beli produk skincare luar negeri. Proceeding of Industrial Research Workshop and National Seminar, 12, 1068–1072. Hafez, M. (2021). The impact of social media marketing activities on brand equity in the banking sector in Bangladesh: The mediating role of brand love and brand trust. International Journal of Bank Marketing, 39(7), 1353–1376. doi:10.1108/IJBM-02-2021-0067 Handayani, T., & Fathoni, M. A. (2021). Pengaruh endorsement terhadap minat membeli produk skin care halal pada mahasiswa Jabodetabek. El-Iqtishod: Jurnal Ekonomi Syariah, 5(2), 75–98. Ibrahim, B., Aljarah, A., & Ababneh, B. (2020). Do social media marketing activities enhance consumer perception of brands? A meta-analytic examination. Journal of Promotion Management, 26(4), 544–568. doi:10.1080/10496491.2020.1719956 Ideswal, I., Yahya, Y., & Alkadri, H. (2020). Kontribusi iklim sekolah dan kepemimpinan kepala sekolah terhadap kinerja guru Sekolah Dasar. Jurnal Basicedu, 4(2), 460–466. doi:10.31004/basicedu.v4i2.381 Imbayani, I. G. A., & Gama, A. W. S. (2018). The Influence of Electronic Word of Mouth (E-Wom), brand image, product knowledge on purchase intention. Jagaditha: Jurnal Ekonomi dan Bisnis, 5(2). Kurniawati, L. M. (2019). Effect of product quality and brand equity on buying interest. Journal of Digital Marketing and Halal Industry, 1(1), 75–82. doi:10.21580/jdmhi.2019.1.1.4369 Ngah, A. H., Gabarre, S., Han, H., Rahi, S., Al-Gasawneh, J. A., & Park, S. (2021). Intention to purchase halal cosmetics: do males and females differ? A multigroup analysis. Cosmetics, 8(1), 19. doi:10.3390/cosmetics8010019 Pasharibu, Y., & Nurhidayah, A. (2021). Digitalization strategies through brand image, celebrity endorser, and EWOM of Indonesian halal product towards a purchase decision. International Journal of Economics, Business and Accounting Research (IJEBAR), 5(3), 2771–2782. doi:10.29040/ijebar.v5i3.3034 Prasetio, A., Rahman, D., Sary, F., Pasaribu, R., & Sutjipto, M. (2022). The role of Instagram social media marketing activities and brand equity towards airlines customer response. International Journal of Data and Network Science, 6(4), 1195–1200. doi:10.5267/j.ijdns.2022.6.014 Schivinski, B., & DÄ…browski, D. (2013). The impact of brand communication on brand equity dimensions and brand purchase intention through Facebook. Journal of Research in Interactive Marketing, 9(1), 31–53. doi:10.1108/JRIM-02-2014-0007 Seo, E.-J., & Park, J.-W. (2018). A study on the effects of social media marketing activities on brand equity and customer response in the airline industry. Journal of Air Transport Management, 66, 36–41. doi:10.1016/j.jairtraman.2017.09.014 Sharma, S., Singh, S., Kujur, F., & Das, G. (2020). Social media activities and its influence on customer-brand relationship: An empirical study of apparel retailers' activity in India. Journal of Theoretical and Applied Electronic Commerce Research, 16(4), 602–617. doi:10.3390/jtaer16040036 Sudaryanto, S., Courvisanos, J., Dewi, I. R., Rusdiyanto, R., & Yuaris, J. R. (2022). Determinants of purchase intention during COVID-19: A case study of skincare products in East Java. Innovative Marketing, 18(1), 181–194. doi:10.21511/im.18(1).2022.15 Victoria, M., & Purwianti, L. (2022). Analisis faktor yang mempengaruhi purchase intention produk skincare dengan mediasi trust pada kalangan generasi Z di Kota Batam. Ekonomis: Journal of Economics and Business, 6(2), 465–475. doi:10.33087/ekonomis.v6i2.572 Wahyuningsih, I. (2018). Intensi konsumen terhadap kosmetik dan produk skincare halal di Indonesia: Pendekatan theory of planned behavior. JEBA (Journal of Economics and Business Aseanomics), 3(1). doi:10.33476/jeba.v3i1.741 Yadav, M., & Rahman, Z. (2018). The influence of social media marketing activities on customer loyalty: A study of e-commerce industry. Benchmarking: An International Journal, 25(9), 3882–3905. doi:10.1108/BIJ-05-2017-0092 Zaki, K., Nopiah, R., Walid, A., & Putra, E. P. (2021). The role of environment in responding to halal skincare products in Indonesia. Journal of Physics: Conference Series, 1796(1), 012030.